PENGARUH PENGALAMAN AUDITOR DAN TIME BUDGET PRESSURE PADA PROFESIONALISME DAN IMPLIKASINYA TERHADAP KINERJA AUDITOR - Anggreni, Ni Wayan Dewi; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 18 No 1 (2017), 2017)
Auditor experience and time budget pressure could affect the performance of auditors through professioalism. The purpose of this study was to determine the effect of auditor experience and time budget pressure on the professionalism and its implications on the performance of auditors in the province of Bali. This research was conducted in the public accounting firm of Bali Province. The samples used were 42 respondents using purposive sampling technique. Methods of data collection is done by using questionnaires, and the data were analyzed using path analysis. Based on the analysis found that the auditor's experience a positive effect on professionalism, auditor's experience and professionalism positive effect on the performance of auditors, time budget pressure negative effect on professionalism, time budget pressure have negative effect on the performance of auditors. Through professionalism, there is an indirect effect on the auditor's experience and time budget pressure on the performance of auditors.
Keywords: Experience Auditor, Time Budget Pressure, Professionalism, And Performance Auditor